-2(8v-2)+4v=6(v+2)

Simple and best practice solution for -2(8v-2)+4v=6(v+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(8v-2)+4v=6(v+2) equation:


Simplifying
-2(8v + -2) + 4v = 6(v + 2)

Reorder the terms:
-2(-2 + 8v) + 4v = 6(v + 2)
(-2 * -2 + 8v * -2) + 4v = 6(v + 2)
(4 + -16v) + 4v = 6(v + 2)

Combine like terms: -16v + 4v = -12v
4 + -12v = 6(v + 2)

Reorder the terms:
4 + -12v = 6(2 + v)
4 + -12v = (2 * 6 + v * 6)
4 + -12v = (12 + 6v)

Solving
4 + -12v = 12 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
4 + -12v + -6v = 12 + 6v + -6v

Combine like terms: -12v + -6v = -18v
4 + -18v = 12 + 6v + -6v

Combine like terms: 6v + -6v = 0
4 + -18v = 12 + 0
4 + -18v = 12

Add '-4' to each side of the equation.
4 + -4 + -18v = 12 + -4

Combine like terms: 4 + -4 = 0
0 + -18v = 12 + -4
-18v = 12 + -4

Combine like terms: 12 + -4 = 8
-18v = 8

Divide each side by '-18'.
v = -0.4444444444

Simplifying
v = -0.4444444444

See similar equations:

| y-2x+(3-z)= | | 164=6(a)+4(b)+4(c) | | 2x^2+x^2-8x-4=0 | | 6.1x+1=5.1x | | 4v-24=9(v-6) | | 32-X=25 | | 10u-7u=21 | | 1+8x=-16+31 | | Y=6x+12+2cosx | | 6y=4x+22 | | 5x^2+5y^2+4y+2=0 | | 4x^2+90x-500=0 | | 2(2k+5)-9k+8+3= | | n(5)=-1-5+4 | | 5x+8x-80=60-7x | | 3(x+4)+1=22 | | 9-25b^2= | | 38-X=10 | | 2.8+2.4(x)=16.6 | | -9-1(9-6x)=3(4x+6) | | -2x+9+3x=3+x+6 | | -1.2(a-2)=0.8(a+7) | | X+(3x+10)=2x+(2x+10) | | 27x^3+36x^2=0 | | 14=0.022x^2+0.25 | | 2x^2-28x=-2x^2-7x-27 | | 29+n=33 | | 3y-5x-1=0 | | -5(-4u-y+2)=(-5)(-4u)-(-5)(y)+(-5)(2) | | x+600+42-88=92 | | y-3.5y-5.4=-2(y-2.8) | | 34y+6y=34y |

Equations solver categories